2022
DOI: 10.1515/hsz-2021-0417
|View full text |Cite
|
Sign up to set email alerts
|

A guide to designing photocontrol in proteins: methods, strategies and applications

Abstract: Light is essential for various biochemical processes in all domains of life. In its presence certain proteins inside a cell are excited, which either stimulates or inhibits subsequent cellular processes. The artificial photocontrol of specifically proteins is of growing interest for the investigation of scientific questions on the organismal, cellular and molecular level as well as for the development of medicinal drugs or biocatalytic tools. For the targeted design of photocontrol in proteins, three major met… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 318 publications
1
12
0
Order By: Relevance
“…IC 50 values determined in the indirect assays indicated that catalytic activity could be regulated about 15-fold by this approach, whereas the direct assay indicated a light-regulation factor of about 5. These values compare favorably with most light-regulation factors reported in the literature and underline the versatility and efficiency of “photoxenoprotein” approaches …”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…IC 50 values determined in the indirect assays indicated that catalytic activity could be regulated about 15-fold by this approach, whereas the direct assay indicated a light-regulation factor of about 5. These values compare favorably with most light-regulation factors reported in the literature and underline the versatility and efficiency of “photoxenoprotein” approaches …”
Section: Discussionsupporting
confidence: 76%
“…These values compare favorably with most light-regulation factors reported in the literature and underline the versatility and efficiency of "photoxenoprotein" approaches. 1 ■ METHODS Strains, Cloning, and Site-Directed Mutagenesis. E. coli BL21 Gold (DE3) and E. coli NEB Turbo cells were used as hosts for protein expression and molecular cloning, respectively.…”
Section: ■ Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the light‐induced change in electronic properties and geometry of the photoresponsive core structure can be harvested to regulate the properties of a bioactive molecule of choice. For instance, photoswitches were applied as light‐controllable antibiotics, [8,9] DNA‐binders, [10,11] microtubule modulators, [12,13] and as enzyme inhibitors [14–16] . Moreover, the large structural change in geometry of the photoswitchable unit can be translated onto a larger structure, such as a biomacromolecule, when incorporated in a strategically suitable position [1] .…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] Moreover, the large structural change in geome-try of the photoswitchable unit can be translated onto a larger structure, such as a biomacromolecule, when incorporated in a strategically suitable position. [1] Thus, it can be used to efficiently alter the properties of, for instance, nucleic acids, [17] peptides, [18] and proteins [14] by use of light as external stimulus. Photoswitches such as (heteroaryl) azobenzenes, [19,20] diarylethenes, [21] and spiropyrans [22] have been studied previously in biological contexts.…”
Section: Introductionmentioning
confidence: 99%